2021
DOI: 10.1017/s0967199421000253
|View full text |Cite
|
Sign up to set email alerts
|

Early embryo morphokinetics is a better predictor of post-ICSI live birth than embryo morphology: speed is more important than beauty at the cleavage stage

Abstract: Given the importance of embryo developmental competence assessment in reproductive medicine and biology, the aim of this study was to compare the performance of fertilization and cleavage morphokinetics with embryo morphology to predict post-ICSI live birth. Data from embryos cultured in a time-lapse microscopy (TLM) incubator and with known live birth outcomes (LB: embryos achieving live birth, n = 168; NLB: embryos not achieving live birth, n = 1633) were used to generate receiver operating characteristic (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Faster tPNf and t2 are believed to be related to embryo morphology on the third day [7]; however, this is not always the case. There are reports that early embryo morphokinetics are better predictors of post-ICSI live births than embryo morphology [6]. Earlier t3, t4, and t5 are related to higher implantation rates, whereas t4 reflects the quality of blastocysts [12,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faster tPNf and t2 are believed to be related to embryo morphology on the third day [7]; however, this is not always the case. There are reports that early embryo morphokinetics are better predictors of post-ICSI live births than embryo morphology [6]. Earlier t3, t4, and t5 are related to higher implantation rates, whereas t4 reflects the quality of blastocysts [12,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, among embryos with appropriate morphology, a considerable proportion (20.1%) showed poor kinetic parameters, accompanied by a severely reduced live birth rate (P < 0:001). Compared to traditional morphology, early morphological dynamics can predict live births more accurately [6]. This indicates that early embryonic morphological dynamics can be used as an important parameter for embryo selection and transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these embryos demonstrated an impaired ability to achieve developmental milestones in vitro and ultimately failed to achieve blastocyst expansion at an appropriate time-point (37) . Early embryo cleavage dynamics have been associated with rates of ongoing development and live birth within clinical ART settings (38) . Recently, the association between being overweight in men and a reduction in fertility has been supported further through a large-scale meta-analysis of 115 158 study participants, revealing obese men had an increased likelihood of infertility (39) .…”
Section: Paternal Nutrition and Reproductive Fitnessmentioning
confidence: 99%
“…To obtain objective, real-time embryo morphologic data with potential clinical relevance, we focused on time-lapse microscopy as a noninvasive method to characterize embryo quality. Many studies have identified parameters associated with improved clinical outcomes, including time of appearance and fading of two pronuclei ( 9 ), the timing of cell cycle events ( 10 , 11 ), the time between 2- to the 8-cell cleavage stage ( 12 , 13 , 14 , 15 ), cleavage events ( 16 ), cytokinesis duration ( 17 ), time to initiation of blastulation ( 18 , 19 , 20 ), and combined morphokinetic and morphologic or molecular parameters ( 21 , 22 , 23 , 24 , 25 , 26 , 27 ). Other studies showed that no differences were found in the time-lapse parameters of euploid embryos that led to miscarriages ( 28 ).…”
mentioning
confidence: 99%